Description of the Knowledge and Attitude of the Nurse in the Wana Anu Center of Giving Early Breastfeeding Initiation (Imd) in Rsud Dr. Had » Sinaga Pangururan, Samosir District 2017 - Firdasari (Institute of Computer Science (IOCS), 2022)
The Early Breastfeeding Initiation Program has enormous benefits for babies and mothers who have just given birth. However, the implementation of early breastfeeding initiation itself has not been socialized in several hospitals, as well as in midwife practice clinics, so its application still needs to be developed. So a research was conducted on the Description of Knowledge and Attitudes of Nurses in the OK Room in Providing Early Breastfeeding Initiation (IMD) in RSUD Dr. Hadrianus Sinaga Pangururan, Samosir Regency, 2017. This research was conducted in May-August 2017 with a population of 10 respondents. Sampling was carried out using total sampling technique, namely all respondents were sampled. The results of this study indicate that the majority have good knowledge, namely 7 people (70%), while the minority have less knowledge, namely 3 people (30%). The majority had an attitude of agreeing as many as 7 people (70%) while the minority disagreed as many as 3 people (30%). It is hoped that the Leaders at Dr. Hadrianus Sinaga Pangururan, both at the director level and head of the room, can supervise the implementation of standard operating procedures for the provision of Early Breastfeeding Initiation in postpartum patients, specifically for post-operative cesarean sections. If necessary, a special officer is appointed who is directly responsible for the implementation of IMD administration to newborns. It is hoped that in the teaching and learning process both in the classroom and in the laboratory the administration of IMD can be mastered by every student. This research can be used as evidence based in conducting research with the same variables or with several variables related to the provision of Early Breastfeeding Initiation (IMD).